The effect of the build orientation and heat treatment on the fatigue and fracture properties of a directed energy deposited nickel-based superalloy (Inconel 718) - Paul, Mikyle (Department of Mechanical Engineering, 2021)
This project focused on determining the effect of build orientation and heat treatment on the fatigue crack growth rate and fracture toughness properties of the nickel-based superalloy, Inconel 718 that has been manufactured by additive manufacturing technique, directed energy deposition (DED). Three different build orientations namely XY, XZ and ZX, in both the as-built and heat-treated conditions were tested through a combination of comparative fatigue crack growth rate (FCGR) and fracture toughness (FT) tests. A heat treatment protocol was applied to the material to relieve residual stress from the building process to homogenise the microstructure and to introduce precipitation hardening to the material for strengthening. This heat treatment protocol consisted of a solution treatment at 1200 °C for 2 hours followed by a water quench. Thereafter an ageing procedure was conducted at 650 °C for 16 hours followed by air cooling. The Paris equation for each build orientation and material condition was determined with the aid of a crack measurement technique that was developed in this project. This technique was designed to significantly improve the measurement accuracy of the fatigue crack during testing. The developed crack measurement system consisted of a digital camera and stereomicroscope that were mounted to the ESH servo-hydraulic testing machine with a rig that was designed and manufactured during this project. The FCGR and FT tests were conducted on compact tension (CT) specimens and the ASTM E647 and ASTM E1820 test standards were used as guidelines to test the specimens respectively. FCGR tests were conducted at a load range of 7.2 kN and a stress ratio of 0.1. The results indicated that there was a significant variation in the fatigue performance with respect to the material's build orientation. The fatigue crack path encountered several deviations during testing, resulting in inconsistent Paris data. FT tests were conducted at a cross-head speed of 2 mm/min (in the range of 0.8 to 2.0 MPa√m/s). The material exhibited an elastic-plastic behaviour and therefore, a J-integral fracture toughness analysis was undertaken. Jmax values (the value of J at the maximum load) were obtained for each build orientation and material condition, and compared. It was seen that the average Jmax values for each build orientation differed, indicating that the build orientation affected the fracture toughness properties of the material. The applied heat treatment protocol homogenised the microstructure of the material and induced precipitation hardening. This was confirmed with the aid of light microscopy and scanning electron microscopy with energy dispersive X-ray spectroscopy, where a high concentration of niobium-rich Laves phase was almost completely eliminated by the heat treatment. The positive effects of the heat treatment on the material were noticed during the FCGR tests as the fatigue crack growth resistance and fatigue life of the material increased. The gradient of the Paris curve, m, was seen to increase from approximately 5 to approximately 8. This effect was also noticed during the FT tests where a uniform increase in Jmax of approximately 50 kJ/m2 was recorded for each build orientation. It was concluded that a post manufacture heat treatment is essential for residual stress relief and homogenisation to occur in IN718 manufactured by DED. The material's response to fatigue is not uniform when in the as-built state for all build orientations due to the presence of the niobium-rich Laves phase. The material displays superior mechanical properties after the heat treatment protocol in terms of fatigue crack growth resistance and fracture toughness when compared to the as-built condition. Furthermore, it was also seen that the build parameters such as scanning width and hatch spacing affected both the fatigue and fracture properties of the material and must therefore also be taken into consideration when producing the material. A successful crack measurement technique and apparatus was also developed that greatly increases the accuracy of Paris data obtained. The XZ orientation was seen to possess the most uniform fatigue and fracture properties amongst the three orientations tested in this project in both the as-built and heat-treated conditions.